Wasserstoff im Straßenverkehr - eine Aufgabe für den Gesetzgeber? - Schwab, Roland; Wolf, Juliane (Deutscher Verkehrs-Verl., 2006)
Die Vielfalt auf den Straßen nimmt zu. Immer mehr Fahrzeuge, die nicht Benzin oder Diesel sondern Wasserstoff tanken, nehmen am alltäglichen Straßenverkehr teil. Mit der Zahl der Fahrzeuge wird die Zahl der Tankstellen wachsen, die den neuen Kraftstoff anbieten. In Berlin gibt es bereits zwei öffentliche Wasserstofftankstellen, in anderen Städten Deutschlands werden weitere folgen. Hinter dieser Entwicklung verbergen sich komplizierte Prozesse. difu

The legal conditions for the introduction of hydrogen as a new vehicle fuel can only be described if the analysis is including non-hydrogen specific legislation, too. Hydrogen is considered as a dangerous a substance as gasoline or diesel in European and German law. The industrial production of these fuels is equally treated. The threshold of stored quantities and the required approval procedures indicate that hydrogen is still considered as chemical product in sharp contrast to gasoline or diesel that are easy to handle in daily operation conditions. The legislation for the transport of dangerous goods permits the transport of hydrogen by road rail or by ship. The on-site production and storage of larger quantities of hydrogen could require a complex approval process involving public hearings and construction allowances only in commercial and industrial areas. The state-of-the-art type approval procedure valid in all European member states resulting in an EU wide type approval for conventional vehicles cannot be applied to hydrogen fueled vehicles today. Presently hydrogen is taxed as a motor fuel according to the national mineral oil tax regimes in most countries. The future market penetration of hydrogen vehicles into the total fleet will also depend on the fact that hydrogen can achieve a tax exemption or relief for a certain time period. difu
Keywords: Öffentlicher Verkehr; Straßenverkehr; Verkehrspolitik; Verkehrsplanung; Verkehrsrecht; Tankstelle; Wasserstoff; Verkehrssicherheit; Umweltschutz; Kraftstoff; Risikomanagement; EU-Richtlinie; Alternativer Kraftstoff